POVERTY AND RELIGIOSITY: THE ‘MISSING LINK’ FROM ISLAMIC PERSPECTIVE - Ahmad Azrin Adnan; Rosdalina Bukido (IAIN Manado, 2020)
Poverty is highly associated with many negative measurable aspects of life. Therefore, it is often regarded as a sign of failure. One of the arguments that prove this premise is that poverty is closer to disbelief. By rejecting doubt to preserve religion, a group that adheres to its logical religion will avoid poverty. Poverty in Kelantan shows the opposite. In a state of extreme religious adherence in terms of understanding, beliefs, and practices, more than half of the poor in Kelantan are hardcore poor. At the same time, the hardcore poor and the poor in Kelantan have the highest number in Peninsular Malaysia. This paper aims to study the relationship between poverty and religiosity in Kelantan. About 3,000 poor in ten provinces in Kelantan selected as respondents through stratified sampling. This study has demonstrated the true definition of poverty which includes the element of soul. It is clearly different from current definitions that focus more on property ownership.